Application and evaluation of hydrodissection in microwave ablation of liver tumours in difficult locations - Yuan Song; Meng Wu; Ruhai Zhou; Ping Zhao; Dan Mao (Frontiers in Oncology, 2023)
ObjectiveTo investigate the safety and mid-term outcomes of hydrodissection-assisted microwave ablation (MWA) of hepatocellular carcinoma (HCC) in various difficult locations.MethodsA total of 131 HCC patients who underwent ultrasound-guided MWA from March 2017 to March 2019 were included. Following ultrasound examination, patients with tumors at difficult locations were treated with hydrodissection-assisted MWA (hydrodissection group), while those with tumors at conventional locations received MWA (control group). Both groups were compared concerning baseline characteristics, ablation parameters, complete ablation rates, and complication rates. Kaplan-Meier curves analyzed local tumor progression and overall survival, with stratified analysis for different difficult locations (adjacent to gastrointestinal tract, diaphragm, and subcapsular tumors). Additionally, Cox regression analyses were conducted to assess the impact of different difficult locations on these outcomes.ResultsComplete ablation rates were similar between the hydrodissection and control groups (91.4% vs. 95.2%, P>0.05). Postoperative complications occurred in three patients, including liver abscess and biliary injury. No significant differences in major or minor complication rates were found between the groups (P>0.05). Local tumor progression was detected in 11 patients (8.4%) at the end of the follow-up period. Neither cumulative local tumor progression rate (P=0.757) nor overall survival rate (P=0.468) differed significantly between the groups. Stratified analysis showed no effect of tumor location difficulty on cumulative local tumor progression or overall survival. Tumor number and size served as independent predictors for overall survival, while minimal ablation margin ≤ 5mm independently predicted local tumor progression. In contrast, the tumor location was not statistically significant. Sensitivity analyses corroborated the robustness of the models.ConclusionHydrodissection-assisted MWA for HCC in various difficult locations demonstrated safe and effective, with complete ablation and mid-term outcomes comparable to those for tumors in conventional locations.